Avaliação da biodisponibilidade de metais em perfis de sedimentos da atividade de carcinicultura na região do baixo São Francisco, SE, Brasil - Xavier, Larissa Santos (2023)
Shrimp farming is defined as raising shrimp in captivity. Due to the growth of activity in the Baixo São Francisco region, the need arose to assess the quality of sediments under the influence of this crop. With this, the objective of the work was to evaluate the chemical profile of metals in sediments, collected in the year 2019, in three shrimp farms, located in order to encompass the Lower São Francisco region, being a profile in the nursery and another profile in the drainage channel, on each farm. In this study, the partial transfer method was used, where the bioavailable concentrations of Ca, Cr, Cu, Fe, K, Mg, Mn, Na, Ni and Zn were determined by ICP OES. Agreement results ranged from 97.59% (Ca) to 117.92% (Mg) for the HISS-1 marine sediment certified reference material (Canada). Relative standard deviation values are below 15%, expressing the accuracy of the method. The granulometric characteristics of the intercalated sediments revealed a predominance of obtaining clay and silt in profiles F1A and F1B, from the farm in Igreja Nova/AL, and silt and fine sand in profiles F2C, F2D, F3E and F3F, from the two farms in Brejo Large /SE. The OM content was above the limit established by CONAMA Resolution No. 454/2012, a limit of 10% for organic matter present in the dredging sediments. Through the application of HCA, it was observed the formation of three groups that present high similarity (I: formed by the F2D profile, II: formed by the F1B and F3E profiles; and III: formed by the F1A, F2C and F3F profiles). With the application of PCA, it was noticed that PC1 represents 41.02% of variance, while PC2 presented 30.21% of variance, with only two first PCs being enough to explain 71.23% of the accumulated variance of the data set , where the F2D profile samples are distributed in the region with positive scores for both PC1 and PC2, being influenced by the elements Ca, Mg and Na, the F1B and F3E profiles are characterized by the highest levels for K and Cr, the F1A profiles , F2C and F3F due to the similarity in the concentrations of Fe, Ni, Mn and Cu. The study indicates low enrichment for Cu and Zn and moderate enrichment for Mn, with shrimp feeding being the main factor responsible for the increase of Cu, Zn and Mn in the sediments. Until the period in which the sediment profile samples were collected, the results of the partial grades indicate that, depending on the concentration for each metal analyzed in the present study, through the VGQS, the negative effects on the biota are observed. And the shrimp farming activity, due to its excellent potential for economic growth, requires investment in technology, innovation and research, associated with the protection and interaction of environmental agencies, so that the activity continues to generate profits and becomes more sustainable.